The Germination and Growth of Two Strains of Bacillus cereus in Selected Hot Dishes After Cooking - Josef Kameník; Marta Dušková; Alena Zouharová; Michaela Čutová; Kateřina Dorotíková; Michaela Králová; Blanka Macharáčková; Radka Hulánková (Foods)
The aim of this study was to assess the germination and growth of two strains of Bacillus cereus following the artificial inoculation of six selected hot dishes with spores which were then stored at temperatures of 40, 50, and 60 °C for 0.5, 1.0, 2.0, 2.5, 3.0, and 4.0 h. The water activity of the prepared meals varied between 0.967 and 0.973 and the salt content between 0.74 and 1.40%. The pH value of four dishes exceeded 6.0, but for two (tomato sauce and ratatouille) it was 4.6. The tested strain DSM 4312 showed good growth abilities and attained a population exceeding 6.0 log CFU/g within 4 h at 40 °C in foods with pH values > 6.0. The study demonstrated that a drop in food temperatures to 40 °C is risky, while no growth of B. cereus was detected within 4 h at 50 and 60 °C. The growth rate of B. cereus is conditioned not merely by environmental conditions (temperature, pH values, food composition), but also by the bacterial strain.